1998
DOI: 10.1007/bf02463424
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms responsible for autocrine regulation of the epiphysis function

Abstract: The effect of injection of exogenous melatonin on formation of the nocturnal peak of the melatonin concentration and intrapineal hormonogenesis was studied on mature male rats. It was shown that 3H-melatonin is selectively uptaken by pinealocytes, and the uptake intensity depends on the degree of saturation of an organism with exogenous melatonin. Exogenous melatonin exerts an inhibitory influence on the hormone self-production, at the same time apparently stimulating synthesis of epiphyseal peptides. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…In this connection of particular interest are the disturbances of the pituitary-thyroid relations occurring in hypothyrosis. It was shown that hypothyrosis causes a drastic decrease in melatonin concentration [6,9].…”
Section: Resultsmentioning
confidence: 99%
“…In this connection of particular interest are the disturbances of the pituitary-thyroid relations occurring in hypothyrosis. It was shown that hypothyrosis causes a drastic decrease in melatonin concentration [6,9].…”
Section: Resultsmentioning
confidence: 99%
“…The data on the effect of the parafollicular apparatus on the processes of synthesis of methoxyindoles in the brain epiphysis indicate that thyrocalcitonin, as compared with Т 3 and Т 4 , suppresses the production of melatonin and 5-methoxytryptamine in pinealocytes [91]. Such oppositely directed effects were observed not only in intact animals but also in animals preliminarily injected with Т 4 [92].…”
Section: Direct Connections and Feedbacks Between The Brain Epiphysismentioning
confidence: 98%
“…According to the existing concepts, biologically active substances of epiphyseal nature are also directly involved, together with TRH and TTH, in the mechanisms underlying central neuroendocrine regulation of morphofunctional activity of the thyroid gland [9,32,[34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%